Pola Komunikasi Trainer dengan Anak Tuli dalam Meningkatkan Kemampuan Berkomunikasi di Gresik - Ismail Hasan (Jurnal Ilmu Komunikasi, 2020)
The problem examined by this study is how the interpersonal communication patterns between trainers and deaf children in the technical implementation unit (UPT) resource center for children with special needs (ABK) in Gresik Regency, East Java Province. The aim of this research is to describe the interpersonal communication patterns between trainers and deaf children in improving their communication skills. This research uses a qualitative approach with descriptive methods. The results of this study indicate that the interpersonal communication patterns carried out by the UPT to ABK are circular communication patterns and primary communication patterns. Early in the process before the implementation of therapy, a holistic approach is carried out on children. The form of learning at the resource center is therapy. To improve language and speaking skills, the therapy is speech therapy. The form of teaching uses Audio Verbal Teraphy.